Pengembangan Media Pembelajaran Aplikasi BASAYA Learning untuk Meningkatkan Pemahaman Keberagaman Sosial Budaya pada Peserta Didik Kelas V - Sofi Fadillah Hendiyani; J. Julia; Rana Gustian Nugraha (Journal on Education, 2023)
This development research aims to: (1) determine the process of developing the learning media for the BASAYA Learning application; (2) to know the effectiveness of the use of learning media in the BASAYA Learning application on Socio-Cultural Diversity material; and (3) knowing the level of practicality of learning media on students after using the BASAYA Learning application on Socio-Cultural Diversity material. The method used in this research is using the Design and Development (D&D) method and using the ADDIE development model which consists of five stages, namely Analysis, Design, Development, Implementation and Evaluation. The results of this study: (a) learning media products for the BASAYA Learning application are produced in the form of an .apk to be opened on a device (an Android-based application) and an .exe file to be opened on a Personal Computer (PC). (b) the products produced are "Very Valid" and "Very Practical" based on the results of assessments from experts validating learning media, materials and language, grade 5 teacher validation, and the results of recapitulation of student tanggapanse angles (c) the products produced are effective in increasing students' understanding of material on socio-cultural diversity in the subject of Citizenship Education. This is evidenced by the average pretest and posttest scores of fifth grade students in the limited test and broad test with the "Medium" N-Gain value category.